Psychological distress among Prisoners in Bagdad city, Iraq - Hussein, Hassan A.; Sachit, Kareem R.; Alwan, Iman H. (International Journal of Psychosocial Rehabilitation, 2020)
Psychological disorders are further common between the prison; No search is known for mental disorders in Iraq’s prisons, and forensic psychiatry services are available for those who suffer from them. This study highlights to determine the rate of psychological distress among prisoners in Iraq. The determination of this study continued to assess the levels of psychological distress amid prisoner in prisons of Baghdad, Iraq. A descriptive study was exposed from January 20th 2020 to May 1st 2020 on prisoners in Baghdad City. Appropriate samples from 100 prisoners chosen from eight prisons in the city of Baghdad. The study uses the self-management questionnaire. Psychological distress was measured using the Kessler Psychological Distress Scale (K10). The data has been analyzed by using the descriptive statistics (Frequencies, Percentages, Means and Standard Deviations (SD) and the inferential statistics (Chi-square to find out the relationships between the socio-demographic and clinical characteristics and the levels of psychological distress). The results of the current study exposed that two-thirds of all defendants suffer from moderate to severe psychological distress and there is a close relationship between age, gender, prison period, and the period of the expiration of the social situation with psychological distress.. The study concluded that the levels of psychological distress among prisoners were moderate to high and there are many variables are positively associated with distress level.